The Relationship of In Vitro Anti-Inflammatory and Antioxidant Activity with Total Phenolic and Flavonoids Content of Tithonia diversifolia Leaves Ethanolic Extract and Fractions - Endah Puspitasari; Nuri Nuri; Siti Muslichah; Bawon Triatmoko; Dewi Dianasari (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2024)
A previous study showed that Tithonia diversifolia ethanolic extract has antiproliferative properties against HeLa cervical cancer cells. It has also shown anti-inflammatory properties in vivo, one of the approaches to cancer chemoprevention. This research aimed to determine the relation of in vitro anti-inflammatory and antioxidant activity of T. diversifolia leaves ethanolic extract and fractions with total phenolic and flavonoid content. The anti-inflammatory was evaluated in vitro using red blood cell (RBC) membrane stabilization and inhibition of protein denaturation method, while antioxidant activity was done using the DPPH method. Phytochemical screening was done using the TLC method. Total phenolic and flavonoid content were also counted using the colorimetry method. ANOVA followed by LSD post hoc, multiple regression analysis, and Pearson correlation were used to analyze the data. Compared to its fractions, the highest anti-inflammatory and antioxidant activity was obtained from T. diversifolia leaves ethanolic extract. The T. diversifolia leaves ethanolic extract contained terpenoids, alkaloids, polyphenols, and flavonoids. Overall, the antioxidant property contributed more to RBC membrane stabilization than protein denaturation inhibition. The phenolic and flavonoid content contributed most to antioxidant and red blood cell membrane stabilization rather than protein denaturation inhibition.